2014
DOI: 10.1002/cbin.10243
|View full text |Cite
|
Sign up to set email alerts
|

A novel estrogen receptor GPER mediates proliferation induced by 17β‐estradiol and selective GPER agonist G‐1 in estrogen receptor α (ERα)‐negative ovarian cancer cells

Abstract: G protein-coupled estrogen receptor (GPER) is recently identified as a membrane-associated estrogen receptor that mediates non-genomic effects of estrogen. Our previous immunohistochemistry study found an association between GPER and the proliferation of epithelial ovarian cancer. However, the contributions and mechanisms of GPER in the proliferation of ovarian cancers are not clear. We have examined the role of GPER in estrogen receptor α (ERα)-negative/GPER positive OVCAR5 ovarian cancer cell line. MTT assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…Several reports have demonstrated that multiple cancer cell lines proliferate in response to the GPER-selective agonist G-1 (36-38) and that E2-dependent proliferation can be reduced upon silencing GPER expression or inhibiting GPER activity (16, 39-41). While these data suggest GPER may promote breast tumor growth, its importance in breast cancer initiation, growth and progression has remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated that multiple cancer cell lines proliferate in response to the GPER-selective agonist G-1 (36-38) and that E2-dependent proliferation can be reduced upon silencing GPER expression or inhibiting GPER activity (16, 39-41). While these data suggest GPER may promote breast tumor growth, its importance in breast cancer initiation, growth and progression has remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to breast cancer cell lines and primary tumors of the breast (Carmeci et al, 1997;Filardo et al, 2000;Revankar et al, 2005;Albanito et al, 2008), GPER is also expressed in cancers and cell lines of the endometrium (Vivacqua et al, 2006a;Leblanc et al, 2007;Smith et al, 2007;He et al, 2009;Petrie et al, 2013;Dai et al, 2014), ovaries (Albanito et al, 2007(Albanito et al, , 2015Henic et al, 2009;Smith et al, 2009;Liu et al, 2014), thyroid (Vivacqua et al, 2006a), lung (Siegfried et al, 2009), prostate (Chan et al, 2010), and testes (Franco et al, 2011). In cell lines of thyroid, ovarian, endometrial, and breast cancers, stimulation of GPER with E2 (Vivacqua et al, 2006a,b;Albanito et al, 2007) or other estrogenic compounds, such as genistein (Vivacqua et al, 2006a), bisphenol A (Dong et al, 2011;Chevalier et al, 2012a), or tamoxifen (Vivacqua et al, 2006b) activates signaling mechanisms that typically promote proliferation.…”
Section: F Cancermentioning
confidence: 99%
“…Even though GPER is widely expressed in tumors, its role in ovarian cancer is controversial. An early report proposed that elevated expression levels of GPER correlate with poor prognosis (19). Activation of GPER in ER-negative cells has also been shown to promote cell migration and invasion (20).…”
Section: G Protein-coupled Estrogen Receptormentioning
confidence: 99%
“…ER-negative cells provide a clear picture of the role of GPER in ovarian cancer cell proliferation. 17β-Estradiol is a strong agonist of GPER that can enhance S-phase promotion and cell migration in ER-negative ovarian cancer cells (19, 20). Selective activation of GPER by G-1 can also activate EGFR, upregulate c-fos, cyclin D1, cyclin E, and cyclin A, and promote cell proliferation (23).…”
Section: G Protein-coupled Estrogen Receptormentioning
confidence: 99%